Original paperSalvage low-dose-rate 125I partial prostate brachytherapy after dose-escalated external beam radiotherapy - Chang, Lynn; Buyyounouski, Mark K. (Journal of Contemporary Brachytherapy, 2014)
Purpose : To report outcomes on 5 patients treated with salvage partial low-dose-rate (LDR) 125-iodine ( 125 I) permanent prostate seed brachytherapy (BT) for biopsy-proven locally persistent prostate cancer, following failure of dose-escalated external beam radiotherapy (EBRT). Material and methods : A retrospective review of the Fox Chase Cancer Center prostate cancer database identified five patients treated with salvage partial LDR 125 I seed implant for locally persistent disease following dose-escalated EBRT to 76-84 Gy in 2 Gy per fraction equivalent. All patients had post-EBRT biopsies confirming unilateral locally persistent prostate cancer. Pre-treatment, EBRT and BT details, as well as post-treatment characteristics were documented and assessed. Results: The median follow-up post-implant was 41 months. All five patients exhibited low acute genitourinary and gastrointestinal toxicities. Increased erectile dysfunction was noted in three patients. There were no biochemical failures following salvage LDR 125 I seed BT to date, with a median post-salvage PSA of 0.4 ng/mL. Conclusions : In carefully selected patients with local persistence of disease, partial LDR 125 I permanent prostate seed implant appears to be a feasible option for salvage local therapy with an acceptable toxicity profile. Further study is needed to determine long-term results of this approach.